2019
DOI: 10.1002/er.4478
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced in situ combustion of heavy crude oil by nickel oxide nanoparticles

Abstract: Summary Nickel oxide nanoparticles were synthesized by microemulsion method and characterized by powder X‐ray diffraction, dynamic light scattering, and scanning electron microscopy. Thermal analyses were performed to identify the influence of nickel oxide nanoparticles on the in situ combustion of Liaohe heavy oil. Low‐temperature oxidation and coking process were investigated by analysing the effluent gases and the fractions of saturates, aromatics, resins, and asphaltenes. Combustion tube tests were also co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…When the temperature rises from 100 to 200 °C, the polymers have a weight loss of about 10%. It indicates that the polymers may absorb the water in the air due to the presence of −NH 2 . With the increase of temperature from 200 to 500 °C, the weight loss of the polymer is close to 80%, which is ascribed to the destruction of the hyperbranched structure.…”
Section: Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…When the temperature rises from 100 to 200 °C, the polymers have a weight loss of about 10%. It indicates that the polymers may absorb the water in the air due to the presence of −NH 2 . With the increase of temperature from 200 to 500 °C, the weight loss of the polymer is close to 80%, which is ascribed to the destruction of the hyperbranched structure.…”
Section: Results and Discussionmentioning
confidence: 96%
“…and it is difficult to treat by traditional methods . Therefore, it is extremely urgent to develop new efficient methods to separate the oil–water emulsion. Demulsification is a significant means to solve the separation problem of an oil–water emulsion in the petroleum and petrochemical industry. At present, the demulsification methods include mechanical demulsification, , electric demulsification, , chemical demulsification, and biological demulsification. …”
Section: Introductionmentioning
confidence: 99%
“…Some nanoparticles of different chemical nature have been employed, including SiO 2 [4,[18][19][20][21], CeO 2 [22][23][24][25][26][27], TiO 2 [28], and Al 2 O 3 [28,29], among others. The materials are characterized as having a high affinity for heavy oil fractions and reducing the asphaltene decomposition temperature near 300 • C. In search of improving their catalytic activity, the benefits of functionalized materials have been reported in the literature, which with low concentrations of transition metal oxides, can reduce the decomposition temperature close to 200 • C. Some of the most used active phases in literature are Ni [18,19,30,31], Pd [18,23,24], Fe [19,26,32], Co [26,33], and Au [34]. Recently, it has been demonstrated that the functionalized nanoparticles improve the conductivity of porous media, and hence, the heat transfer from the steam to the fluids.…”
Section: Introductionmentioning
confidence: 99%
“…These emulsion and wastewater will corrode the surface of the pipeline and make the catalyst toxic in the distillation process and pollute the environment. Therefore, it is extremely urgent to develop new high‐efficiency O/W crude demulsifier to adapt to oilfield construction and development …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is extremely urgent to develop new high-efficiency O/W crude demulsifier to adapt to oilfield construction and development. [5][6][7][8] At present, many studies have been carried out on conventional demulsification methods, including the thermal method, electrical method, and chemical demulsification method. 9 Thermal and electrical methods sometimes also require to add the efficient chemical demulsifier to assist in demulsification, such as polyether demulsifier, 10 nonpolyether demulsifier, 11 siloxane demulsifier, 12 ionic liquid demulsifier, 13 cellulose polymer demulsifier, 14 hyperbranched polymer demulsifiers, 15 and composite demulsifier obtained by compounding two or more kinds of demulsifiers.…”
Section: Introductionmentioning
confidence: 99%